Pengaruh Prestasi Akademik Dan Dukungan Orang Tua Terhadap Resiliensi Akademik Mahasiswa - Putri Kusuma; Vira Sandayanti; Asri Mutiara Putri; Dessy Hermawan (Program Studi Psikologi Islam, 2025)
Final-year university students often face complex academic pressures, especially during the thesis-writing process, which requires sufficient academic resilience. This study aims to examine the influence of academic achievement and parental support on the academic resilience of final-year students. A quantitative approach was employed using the Two Way ANOVA analysis technique. The sample consisted of 217 final-year students from six universities in Bandar Lampung, selected through accidental sampling. The results showed no significant joint effect of academic achievement and parental support on academic resilience. Partially, academic achievement did not significantly influence academic resilience, whereas parental support had a significant effect on academic resilience. These findings highlight the crucial role of parental support in fostering academic resilience among students completing their under-graduate thesis. Keywords : academic resilience, academic achievement, parental support, final-year student, under-graduate thesis